The Development of the Mesenteric Model of Abdominal Anatomy - Byrnes, Kevin Gerard; Cullivan, Orla; Walsh, Dara; Coffey, J. Calvin (Clinics in Colon and Rectal Surgery, 2022)
Recent advances in mesenteric anatomy have clarified the shape of the mesentery in adulthood. A key finding is the recognition of mesenteric continuity, which extends from the oesophagogastric junction to the mesorectal level. All abdominal digestive organs develop within, or on, the mesentery and in adulthood remain directly connected to the mesentery. Identification of mesenteric continuity has enabled division of the abdomen into two separate compartments. These are the mesenteric domain (upon which the abdominal digestive system is centered) and the non-mesenteric domain, which comprises the urogenital system, musculoskeletal frame, and great vessels. Given this anatomical endpoint differs significantly from conventional descriptions, a reappraisal of mesenteric developmental anatomy was recently performed. The following narrative review summarizes recent advances in abdominal embryology and mesenteric morphogenesis. It also examines the developmental basis for compartmentalizing the abdomen into two separate domains along mesenteric lines.
Keywords: mesentery; peritoneum; abdomen; anatomy; embryology